Does increased serum d-lactate mean subclinical hyperpermeability of intestinal barrier in middle-aged nonobese males with OSA?. Issue 49 (December 2017) - Heizati, Mulalibike; Li, Nanfang; Shao, Liang; Yao, Xiaoguang; Wang, Yingchun; Hong, Jing; Zhou, Ling; Zhang, Delian; Chang, Guijuan; Abulikemu, Suofeiya
Abstract : Abstract: Few attention has been directed to the potential effects of intermittent hypoxia experienced in obstructive sleep apnea on the integrity and permeability of intestinal barrier, particularly in adults. Therefore, we evaluated alteration in serum d-lactate concentration in middle-aged males with obstructive sleep apnea to value permeability of intestinal barrier. In this current cross-sectional study, consecutive 159 males were studied. Obstructive sleep apnea was determined by polysomnography and apnea hypopnea index ≥15 event/h was defined as obstructive sleep apnea. D-lactate, lipopolysaccharide binding protein, interleukin-1β, interleukin-6 and tumor necrosis factor-α by ELISA method. Nonobese obstructive sleep apnea (OSA) males showed significantly higher serum d-LA than did nonobese [1374.35 (816-1735) μg/L vs 1166.43 (730–1815) μg/L, P = .018], and obese non-OSA ones [1374.35 (816-1735) μg/L vs 1188.75 (736–1557) μg/L, P = .045], whereas serum LBP levels showed no differences within groups. Serum IL-1β was also slightly higher in nonobese OSA males, but with statistical significance, than in nonobese (19.39 ± 4.67 ng/L vs 17.25 ± 3.66 ng/L, P = .041), and obese non-OSA ones (19.39 ± 4.67 ng/L vs 17.42 ± 3.79 ng/L, P = .047), whereas other biomarkers, IL-6 and TNF-a did not show significant differences among groups. In stepwise multiple linear regression analysis, serum d-LA was independently positively associated with AHI ( B = 5.577, P = .022), and ODI3 ( B = 4.550, P = .024) and negatively with LSaO2 ( B = −12.234, P = .019). Finally, we arrived at a conclusion that serum d-lactate was increased in nonobese middle-aged males with obstrutive sleep apnea, possibly suggesting existence of subclinical disruption of intestinal barrier, and showed significant associations with inflammatory mediators, possibly being involved in systemic inflammation of obstructive sleep apnea.